Dissolution of Foundations Based on Law No. 28 of 2004: Legal Analysis and Practice in Indonesia - Yunus, Nur Rohim; Aji, Ahmad Mukri; Mukri, Syarifah Gustiawati (SALAM: Jurnal Sosial dan Budaya Syar-i, 2024)
Foundations as non-profit legal entities strategically support social, religious, and humanitarian activities in Indonesia. However, in practice, many foundations experience stagnation, deviations from their goals, or are misused, requiring dissolution. This study aims to analyse the legal provisions regarding the dissolution of foundations as stipulated in Law Number 28 of 2004 concerning Foundations, and to evaluate the practices and obstacles in their implementation in the field. The research method used is normative legal research with a statutory and conceptual approach. Data were reviewed through a literature study of relevant laws and regulations, jurisprudence, and previous research results related to the dissolution of foundations. The study results indicate that the dissolution of foundations is regulated normatively in Articles 62 to 71 of the Foundation Law, which include dissolution due to the expiration of the term, the objectives achieved, or based on a court decision. However, in practice, many foundations still do not carry out the dissolution process under legal provisions, including weak supervision, minimal understanding of the law by the management, and suboptimal reporting and liquidation mechanisms. In addition, there is no transparent and accountable system in managing the remaining assets of dissolved foundations.Keywords: Foundation; Dissolution; Foundation Law; Legal Entity; Liquidation